2013
DOI: 10.1080/09712119.2013.795896
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of dietary threonine requirement for growth and immune responses of broilers

Abstract: This study was conducted to determine the effects of supplementing threonine (Thr) at different levels in the diets on growth performance and immune responses of broiler chickens challenged with infectious bursal disease (IBD) and also to estimate Thr requirement based on different response criterion. A total of 300 one-day-old male broiler chicks were assigned to one of the six dietary treatments. Chickens were fed eight graded levels of Thr: 0.60, 0.67, 0.74, 0.81, 0.88 or 0.95% from day 21 to 42 of age. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
4
10
0
Order By: Relevance
“…The increased spleen weight of broilers in this study supports the significant increased antibody titre against SRBC after Arg supplementation. Lymphoid organs in this trial remained unaltered following Thr administration that is in agreement with findings reported in some other experiments (Rao et al 2011;Taghinejad-Roudbaneh et al 2013;Azzam and El-Gogary 2015) Research evaluating the effect of Arg and Thr on leukocyte population is sparse. In the present trial, blood leukocyte counts were not influenced through Arg and Thr in ovo administration.…”
Section: Discussionsupporting
confidence: 92%
“…The increased spleen weight of broilers in this study supports the significant increased antibody titre against SRBC after Arg supplementation. Lymphoid organs in this trial remained unaltered following Thr administration that is in agreement with findings reported in some other experiments (Rao et al 2011;Taghinejad-Roudbaneh et al 2013;Azzam and El-Gogary 2015) Research evaluating the effect of Arg and Thr on leukocyte population is sparse. In the present trial, blood leukocyte counts were not influenced through Arg and Thr in ovo administration.…”
Section: Discussionsupporting
confidence: 92%
“…The weights of the bursa and spleen remained unaltered by the dietary inclusion of L-Thr or stocking density. Results are in agreement with those presented by others (Kidd et al, 2001;Taghinejad-Roudbaneh et al, 2013). Also, Rao et al (2011) found that lymphoid organ (bursa, spleen and thymus) weights and immune responses were not affected by supplementation of L-Thr.…”
Section: Resultssupporting
confidence: 82%
“…Our results may be related to optimal hygienic conditions. Recently, Taghinejad-Roudbaneh et al (2013) reported that Thr requirement under stress and non-hygienic conditions was 0.81% for support growth performance. Also, Corzo et al (2007) concluded that the Thr need to maximize growth performance was 0.71-74% on new litter and for used litter growth performance was maximized at 0.73-0.78%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In laying quails, egg production, the egg weight, and FCR were improved by increasing the Thr concentration in the diet [25] Similar findings have been obtained in meat-type birds, including turkey toms [5], Japanese quails [6], and Pekin ducks from 1 to 21 days of age [8] and from 15 to 35 days of age [9], where the average daily weight gain and FCR increased significantly with the dietary Thr concentration. Furthermore, in chickens challenged with infectious bursal disease, the body weight gain and FCR were improved significantly by increasing the Thr concentration in the diet [7]. Moreover, fertilized eggs injected with Thr on day 14 of incubation exhibited significant improvements in their body weight gain and FCR after the chickens hatched and they were fed the same diet (without Thr supplementation) for 28 and 42 days of age [10,11].…”
Section: Resultsmentioning
confidence: 99%